Annual Plant Reviews Online 2018
DOI: 10.1002/9781119312994.apr0476
|View full text |Cite
|
Sign up to set email alerts
|

The Fate ofACCin Higher Plants

Abstract: The fate of 1‐aminocyclopropane‐1‐carboxylate (ACC), generated by the activity of ACC synthase (ACS), is reviewed. In higher plants, ACC undergoes two known fates – the first being malonylation to form malonyl‐ACC (M‐ACC), and the role of this conjugation step as a reversible one to generate free ACC is considered. The second fate is oxidation to form ethylene and HCN. The metabolism of HCN by β‐cyanoalanine synthase (β‐CAS) is considered, including an emerging view of a role for HCN as a signalling compound i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 159 publications
0
8
0
Order By: Relevance
“…The plant produced ACC is converted to ET by the action of the enzyme ACO, which is also encoded by a multigene family in higher plants ( Dorling and McManus, 2012 ; Ruduś et al, 2013 ). In Arabidopsis , a total of five ACO genes are found, however only ACO2 and ACO4 have been studied in detail ( Gómez-Lim et al, 1993 ; Raz and Ecker, 1999 ; Ramonell et al, 2002 ; Raghavan et al, 2006 ; Linkies et al, 2009 ).…”
Section: Plant Acc and Et Biosynthesis And Signaling Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…The plant produced ACC is converted to ET by the action of the enzyme ACO, which is also encoded by a multigene family in higher plants ( Dorling and McManus, 2012 ; Ruduś et al, 2013 ). In Arabidopsis , a total of five ACO genes are found, however only ACO2 and ACO4 have been studied in detail ( Gómez-Lim et al, 1993 ; Raz and Ecker, 1999 ; Ramonell et al, 2002 ; Raghavan et al, 2006 ; Linkies et al, 2009 ).…”
Section: Plant Acc and Et Biosynthesis And Signaling Mechanismsmentioning
confidence: 99%
“…These studies revealed that ACO is induced in several plant tissues by numerous treatments, such as, wounding, ethrel (a liquid compound that is transformed into ET), Fe 2+ , 2,4-dichlorophenoxyacetic acid and ACC. Likewise, several studies have demonstrated the induction of ACO gene expression by biotic and abiotic stresses, phytohormone treatments (including ET) and developmental and ontological cues in other plant species (reviewed by Dorling and McManus, 2012 ).…”
Section: Plant Acc and Et Biosynthesis And Signaling Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ethylene biosynthetic pathway is accomplished in mainly two rate-limiting steps coordinated by ACS (converts SAM, S-adenosylmethionine, to ACC) and ACO (converts ACC to ethylene) 43 . Genes encoding both enzymes belong to multigene families, whose transcription exhibit temporal-spatial pattern depending on external and internal stimuli 43 .…”
Section: Resultsmentioning
confidence: 99%
“…The ethylene biosynthetic pathway is accomplished in mainly two rate-limiting steps coordinated by ACS (converts SAM, S-adenosylmethionine, to ACC) and ACO (converts ACC to ethylene) 43 . Genes encoding both enzymes belong to multigene families, whose transcription exhibit temporal-spatial pattern depending on external and internal stimuli 43 . The transcriptional regulation of ACS and ACO influences ethylene emission 43 , particularly the increase in ACO expression accompanied by protein accumulation or high enzyme activity is a strong indicator of auto-regulation of ethylene production within a tissue 43 44 .…”
Section: Resultsmentioning
confidence: 99%